Early diagnosis and risk factors of diabetic peripheral neuropathy in type 1 diabetes: insights from current perception threshold testing - Zhao, Qian; Wang, Jialin; Liu, Fangfang; Jiang, Hongwei; Ma, Yujin (Frontiers in Endocrinology, 2025)
ObjectiveThis study investigates nerve fiber dysfunction in type 1 diabetes (T1D) patients and identifies risk factors for diabetic peripheral neuropathy (DPN). It evaluates the relationship between current perception threshold (CPT) tests and nerve conduction velocity (NCV), and assesses CPT’s diagnostic accuracy for early DPN detection.Research design and methodsThis study enrolled 110 patients with T1D and 26 healthy controls between January 2020 and December 2021, in accordance with predefined inclusion/exclusion criteria. CPT testing at 2000 Hz, 250 Hz, and 5 Hz assessed Aβ, Aδ, and C fiber function, while NCV was measured in 47 patients. Subgroups were stratified by disease duration (>5 years vs ≤5 years). Multivariate logistic regression identified DPN risk factors, and CPT-NCV correlation was analyzed using Chi-square and Kappa tests. Receiver operating characteristic (ROC) curves evaluated CPT diagnostic efficacy.ResultsThe incidence of DPN in 110 T1D patients was 78%, with no significant difference between disease duration subgroups (78.3% vs. 78.0%). Neurological abnormalities were significantly more common in the lower extremities compared to the upper extremities (67.27% vs. 49.09%, P < 0.05). Multivariate logistic regression analysis revealed that a waist-to-hip ratio (WHR) greater than 0.85 was an independent risk factor for DPN (OR = 3.01, 95% CI: 1.03-8.80, P < 0.05). Patients with a disease duration >5 years demonstrated significantly higher 2000Hz abnormality rates (68.09% vs. 46.15%, P < 0.05) and more severe neurological lesions (57.45% vs. 35.90%, P < 0.05). In contrast, those with disease duration ≤5 years exhibited elevated 5Hz abnormality rates (30.77% vs. 10.64%, P < 0.05) with predominantly milder lesions (56.41% vs. 31.91%, P < 0.05). Statistical analyses demonstrated a significant association between CPT and NCV (P<0.001), with moderate diagnostic consistency further supported by Cohen’s Kappa Test (κ=0.515, P<0.001). ROC curve analysis demonstrated that CPT exhibited moderate diagnostic accuracy in detecting DPN at the 5Hz, with an area under the curve (AUC) of 0.723.ConclusionsCPT showed moderate diagnostic accuracy for early unmyelinated (C) fibers detection, routine CPT screening in high-risk groups (central obesity/short disease duration) enables timely intervention to prevent irreversible damage.